Modified LPE system used to diffuse Cd to obtain InSb infrared detectors - Guimaraes, Sonia; de Lima, Joaquim Tavares [UNESP]; Petoilho, Jose Carlos; de Lucena, Emerson Ferreira [UNESP]; Hwang, Miriam Kasumi; Campos, Elson [UNESP] (Elsevier B.V., 2008)
We are presenting here p/n junctions obtained with a modified opened liquid-phase epitaxy (LPE) system, used to diffuse indium antimonide (InSb) doped with Cd over InSb doped with Te wafers, in order to make InSb infrared (IR) sensors. This technique has several advantages: the diffusion can be performed in bigger substrate areas improving the device production; this method decreases the device manipulation, decreasing human mistakes and increasing the process reproducibility. The opened LPE in this work produced sensors in the first case with vapor of the diffusion material, coming from a microholed carbon boat full of the diffusion material, over which is positioned the substrate at atmospheric pressure. In the second, the diffusion material is on the bottom of a quartz recipient, and the InSb/Te wafer works as its cover, and vacuum was used. The IR sensors produced with the first method measured 8.9 x 10(7) cm Hz(1/2)/W as detectivity value and higher IR spectral response at 4.6 mu m, and those produced with the second 2.8 x 10(9) cm Hz(1/2)/W, at 4.4 mu m. Besides the electrical-optical properties, the structural properties of diffused layers were investigated by X-ray diffraction (XRD), scanning electron and atomic force microscopy (SEM, AFM), energy-dispersive and secondary ion mass spectroscopy (EDS, SIMS). (C) 2007 Elsevier B.V. All rights reserved.
Keywords: atomic force microscopy; optical microscopy; X-ray diffraction; vapor phase epitaxy; InSb; Te; Cd compounds; homojunctions semiconductor infrared devices